(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Common palm civet has another name “musang luwak” and is included in the Viverridae family. A civet is a small mammal that lives at night (nocturnal) and likes to eat fruit (frugivorous). The population of this animal is spread across Indonesia, Sri Lanka, India, and some South East Asia countries. Osteological studies on civets have not been done much. This study aims to determine the anatomical structure of the mandible and teeth macroscopically. This study used 3 civet craniums with an average body weight of around 2 kg obtained from Yogyakarta and Lampung. The samples separated from the muscles and tissues to obtain the cranium, mandible, and teeth. The cleaned samples were then put in 5.25% Sodium Hypochlorite for 24 hours to make the measurement easier. The next process is rinsing with running water and drying. Morphological studies were carried out by examining the teeth of the civet and comparing them with carnivores in the literature. Morphological craniomandibular data were observed specifically for the existing formations. In the mandible, there is a characteristic formation at the angle of the mandible which is tapered and the teeth are pyramidal in shape with the carnassial part which is a pair of pointed upper and lower teeth used for cutting food. The last two molars have a more sloping shape because they are closely related to the function of crushing bones. The dental formula in civets was formulated by incisivus (3), caninus (1), premolars (4), and molars (2) with a total of about 40 permanent teeth. Keywords: Common Palm Civet, Craniomandibular; Gross anatomy; Osteo morphology, Teeth